Models of Bontebok (Damaliscus pygargus pygargus, Pallas 1766) habitat preferences in the Bontebok National Park and sustainable stocking rates - Luyt, Eustatius du Chavoux (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2005.